Replacement of Analog Automatic Voltage Regulator using Digital Technology - Ersalina Werda Mukti; Sulistyo Wijanarko; Anwar Muqorobin (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Before the 90’s, many power plants in Indonesia were equipped with analog controllers and now those power plants are still in operation to produce electricity. One of those controller parts is Automatic Voltage Regulator (AVR). If a failure occurs in the AVR, the economic solution is by replacing the damaged electronic component with new component. However this method will not solve the problem if the components are not available in local market or become obsolete. Purchasing the new AVR that compatible with other controller parts cannot be done again because the analog controllers are no longer produced by the vendor. Furthermore, replacement of all the controllers with the current technology become expensive.  According to this, an alternative solution is proposed in this paper by designing an AVR that compatible with other controller parts and considering the availability of the electronic components in local market. ATmega8 microcontroller is used to implement a digital AVR and employing op amp based as its signal conditioning. The result shows that the digital AVR can reduce hardware size and power consumption. The digital AVR also meets the computation rate of the computation signal.